The nature of chronic rejection after lung transplantation: a murine orthotopic lung transplant study - Heigl, Tobias; Kaes, Janne; Aelbrecht, Celine; Serré, Jef; Yamada, Yoshito; Geudens, Vincent; Van Herck, Anke; Vanstapel, Arno; Sacreas, Annelore; Ordies, Sofie; Frick, Anna; Saez Gimenez, Berta; et al. (Frontiers in Immunology, 2024)
Chronic rejection is a major complication post-transplantation. Within lung transplantation, chronic rejection was considered as airway centred. Chronic Lung Allograft Dysfunction (CLAD), defined to cover all late chronic complications, makes chronic rejection from an immunological perspective enigmatic. This study investigated the true nature, timing and location of chronic rejection as a whole, within mouse lung transplantation. 40 mice underwent an orthotopic left lung transplantation, were sacrificed at day 70 and evaluated by histology and in- vivo- µCT. For timing and location of rejection, extra grafts were sacrificed at day 7, 35, 56 and investigated by ex- vivo- µCT or single cell RNA (scRNA) profiling. Chronic rejection originated as innate inflammation around small arteries evolving toward adaptive organization with subsequent end-arterial fibrosis and obliterans. Subsequently, venous and pleural infiltration appeared, followed by airway related bronchiolar folding and rarely bronchiolitis obliterans was observed. Ex- vivo- µCT and scRNA profiling validated the time, location and sequence of events with endothelial destruction and activation as primary onset. Against the current belief, chronic rejection in lung transplantation may start as arterial response, followed by venules, pleura and only in a late stage in bronchioles as may be seen in some but not all patients with CLAD.